Perceptions of Older Adults, Hematologists, and Medical Oncologists in Cancer Care. Issue 4 (April 2016) - Barginear, Myra F.; Kozikowski, Andrzej; Pekmezaris, Renee; Akerman, Meredith; Gopal, Naveen; Goldberg, Bradley; Carney, Maria T.; Wolf-Klein, Gisele
Abstract : Objectives: The purpose of this study was to assess and compare the perceptions of hematologists, medical oncologists, cancer patients aged 65 years and older, and family members/caregivers regarding the value of a geriatric assessment (GA) in the management of older adults with cancer. Methods: Participants included adults with cancer aged 65 years and older (n = 66), patient family members/caregivers (n = 32), and physicians (n = 42). A patient survey, a caregiver/family survey, and an online physician survey targeted to hematologists and medical oncologists were distributed at a large cancer center in a major academic health system in the New York metropolitan area. The χ 2 test or the Fisher exact test was used to compare the cohorts for responses to geriatric domains in a GA. Results: Comparisons for each of the 17 GA domains between patient and family member and caregiver responses showed concordance, except for the perception of comorbidities; 16.7% of patients indicated that comorbidities were an issue, compared with 29.0% of family/caregivers ( P = 0.047). Physicians indicated that a GA would be most helpful in addressing cognitive impairment (91.4%), falls (91.4%), and functional status (88.6%). Conclusions: A GA would be useful for physicians and older adults with cancer. Hematologists and medical oncologists recognize the utility of a GA and are receptive to a multidisciplinary geriatrics–oncology collaboration. Abstract : The incorporation of a geriatric assessment (GA) for patients with cancer has shown to be associated with decreased levels of distress, improvement in physical and cognitive functioning, and reduction in mortality. Despite the benefits of GAs, they are not commonly taught in oncology training or used in oncology practice. The primary objective of this study was to identify perspectives among hematologists, medical oncologists, older patients with cancer, and their families and/or caregivers concerning the utility of a GA.